Pengaruh Pemasaran Relasional terhadap Loyalitas Pelanggan pada PT. CABS Inti Inovasi - Porta, Hafiq Gani; Mutmainah, Isbandriyati; Yulia, Iis Anisa (Universitas Medan Area, 2023)
The purpose of this research is to examine and analyze the influence of relational marketing on customer loyalty at PT CABS Inti Inovasi. The population of this study comprises all customers who have made multiple purchases of CABS Inti Inovasi products. The research sample is a subset of the population selected using non-probability sampling, specifically convenience sampling. The data used in this study are primary data collected through the distribution of questionnaires to the selected respondents. The analytical method employed to address this research is multiple linear regression, with marketing dimensions including trust, bonding, empathy, and reciprocity as independent variables, and customer loyalty as the dependent variable. Using 251 respondents, the research findings indicate that trust, bonding, empathy, and reciprocity have a positive and significant partial effect on customer loyalty, with bonding variabel having the most significant impact. Furthermore, the results also demonstrate that trust, bonding, empathy, and reciprocity collectively have a significant influence on customer loyalty.